In Asian America. - Jacoby, Tamar (Commentary)
Presents a commentary on the growth of the Asian American community in the United States (U.S.). Several areas in the U.S. dominated by Asians; Nature of differences within the Asian community; Two self-imposed obstacles in the path to assimilation; Asian naturalization rate.